CORPORATIZATION OF UKRAINE’S CRITICAL INFRASTRUCTURE STATE ENTERPRISES: INSTITUTIONAL ISSUES AND INTERNATIONAL LESSONS - Magomedov, Andriy (Public Management and Policy, 2026)
The article is devoted to the study of the model of corporatization of state-owned enterprises of the critical infrastructure of Ukraine under martial law and post-war reconstruction. Based on the analysis of the cases of NPC Ukrenergo (scandal with 63 unfulfilled contracts for UAH 4.3 billion) and the restoration of water supply to Mykolaiv (corruption risks, delays of more than three years), systemic flaws were identified: political interference in the work of supervisory boards, low financial discipline, and lack of effective due diligence. The transitional provisions of Law No. 5593-d are considered, which retain the Cabinet of Ministers’ control over the financial indicators of state-owned enterprises, which creates a conflict of interest. The positive experience of Costa Rica (state-owned company ICE under the solidarity model, 100% electricity coverage), Uruguay (horizontal integration of service agencies, constitutional ban on water privatization), and Indonesia (IMF fiscal monitoring tool – Health Check Tool) is involved. The recommendations are substantiated: introduction of mandatory due diligence for CI investment projects, development of regionally differentiated performance indicators, and strengthening the role of the public in monitoring corporatized structures.